Vorschläge für eine geochronologische Gliederung des Holozäns in Europa - G. Lüttig (Eiszeitalter und Gegenwart, 1960)
Proposals for the time-stratigraphic subdivision of the Holocene in Europe. The progress in geochronology (varve-counting, dendrochronology, C 14-dating, etc.) makes an accurate delimination of the sub-units of the Holocene possible. A standard division should be compiled. We propose to fix chronologically (e.g. by C 14) the boundaries of sections found through biostratigraphic methods, and to reexamine chronologically the local lithostratigraphic-biostratigraphic divisions of Europe and to add these to the reference scheme. For a standard subdivision, a part of southern Jutland is proposed because here, the dating of the beginning of each biostratigraphic (forest historical) section is possible. This scheme might then be linked with the events of the marine facies-region. The boundaries of the pollen zones should here be reexamined by chronological methods. The names of the sub-sections of the Holocene should in the future be applied as follows: a) to time-units coinciding in time with the sections of the standard-subdivision, b) to sub-units of the Holocene which are based on local litho- or biostratigraphic differences. For the standard-subdivision, it is proposed to determine the boundaries as follows (each in the pollen diagrams of reference area): Beginning of the Young Holocene - beginning of the pollen zone of the Sub-Atlanticum; Beginning of the Middle Holocene - beginning of the pollen zone of the Atlanticum; Beginning of the Old Holocene - beginning of the pollen zone of the Pre-Boreal. New stage-notions should be substituted for the Blytt-Sernander nomenclature.